1994
DOI: 10.2190/4yyh-9xau-wqf9-apvt
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Confidant and a Peer Group on the Well-Being of Single Elders

Abstract: A study of 100 elderly people was carried out to compare the predictions of well-being derived from the confidant model with those derived from the Weiss model. The confidant model predicts that the most important feature of a person's social network for the well-being of that person is whether or not the person has a confidant. The Weiss model states that different persons are needed to fulfill the different needs of the person and in particular that a confidant is important to the need for intimacy and emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 10 publications
4
35
1
Order By: Relevance
“…Given the health benefits of having a confidant or positive support (Gupta andKorte 1994, Thoits 1995), it is not surprising that the presence of a spouse or significant other colours women's perceptions of the disruptive nature of HIV/AIDS. More than half (52 per cent) of the women who were in a monogamous intimate relationship at the time of the interview reported that other assaults were more disruptive than HIV infection.…”
Section: The Relative Impact Of Assaultsmentioning
confidence: 99%
“…Given the health benefits of having a confidant or positive support (Gupta andKorte 1994, Thoits 1995), it is not surprising that the presence of a spouse or significant other colours women's perceptions of the disruptive nature of HIV/AIDS. More than half (52 per cent) of the women who were in a monogamous intimate relationship at the time of the interview reported that other assaults were more disruptive than HIV infection.…”
Section: The Relative Impact Of Assaultsmentioning
confidence: 99%
“…However, this study did not find a significant association between selfreported physical activity levels and life satisfaction among this sample of frail older adults. It is not impossible that the significant association between self-report physical conditions and life satisfaction observed in previous studies (Gupta and Korte 1994;Usui et al 1985) may not exist with a sample of exclusive frail older adults. However, given the limited generalizability of this study, further research is needed in order to fully understand the relationship between self-reported physical activity levels and life satisfaction among frail older adults.…”
Section: Discussionmentioning
confidence: 85%
“…Although previous research supported the importance of including health in life satisfaction studies, there has not been a consistent definition or measure of health. Generally speaking, in gerontological studies of subjective well-being, health has often been conceptualized as: (1) self evaluation of, or perceived, health status (e.g., Donnenwerth and Peterson 1992;Markides and Martin 1979;Russell 1990;Tran 1992), (2) satisfaction with one's own health (e.g., Krause 1991), or (3) self-report physical/activity conditions (e.g., Gupta and Korte 1994;Usui et al 1985). The current study uses all three definitions of health in exploring the relationship between quality of care of geriatric case management and quality of life (life satisfaction, in this case).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In this respect, Gupta and Korte (1994) found that both confidant and peer group variables contributed equally to well-being and health in their study of elderly people. However, Chappell and Badger (1989) cite evidence for the differential impact of subjective versus objective aspects of isolation, noting that emotional isolation (absence of a confidant) is more detrimental than social isolation (limited social network contacts).…”
Section: Life Satisfactionmentioning
confidence: 96%
“…Health status has been found to be one of the strongest predictors of life satisfaction relative to other psychosocial variables Bowling, Farquhar, & Brown, 1991;Gupta & Korte, 1994;Lubben, 1989). This is not surprising in that physical problems and associated functional disability interfere with participation in daily activities and social interactions, two variables also predictive of life satisfaction (Bowling, Farquhar, Grundy, & Formby, 1993).…”
Section: Life Satisfactionmentioning
confidence: 99%